2019
DOI: 10.1097/md.0000000000014888
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, randomized, double-blind, placebo-controlled trial evaluating the efficacy and safety of Huangqi Guizhi Wuwutang granule in patients with rheumatoid arthritis

Abstract: Background:Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by swelling, pain, and synovial damage. Effective methods lack in the treatment of RA. A traditional prescription in use for thousands of years in China, Huangqi Guizhi Wuwutang granule (HGWG) is still chosen to relieve pain and prevent joint malformation in RA patients. However, no evidence-based medical research has been organized to assess the effectiveness and safety of HGWG for RA.Methods/design:We will conduct a multicente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Biologically, the involvement of Chinese herbal medicine induces multiple treatment pathways and mechanisms especially single herb can contain various kinds of active ingredients targeting RA-related receptors and biomarkers ( Chen et al, 2004 ; van der Greef et al, 2010 ; Seca and Franconi, 2018 ). With human clinical trials and animal studies suggested the efficacy and safety of IM with Chinese herbal medicine and their extractions ( Liu et al, 2018 ; Wang et al, 2019 ), IM approaches are expected to motivate improvements in RA treatments strategies and outcomes. Moreover, as biological agents for rheumatoid arthritis are gradually under consideration for national health insurance coverage, we look forward to investigating the role of biological agents in IM treatment strategies in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Biologically, the involvement of Chinese herbal medicine induces multiple treatment pathways and mechanisms especially single herb can contain various kinds of active ingredients targeting RA-related receptors and biomarkers ( Chen et al, 2004 ; van der Greef et al, 2010 ; Seca and Franconi, 2018 ). With human clinical trials and animal studies suggested the efficacy and safety of IM with Chinese herbal medicine and their extractions ( Liu et al, 2018 ; Wang et al, 2019 ), IM approaches are expected to motivate improvements in RA treatments strategies and outcomes. Moreover, as biological agents for rheumatoid arthritis are gradually under consideration for national health insurance coverage, we look forward to investigating the role of biological agents in IM treatment strategies in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…One trial has studied the change in AIS scores in patients with RA after acupuncture therapy, and several upcoming intervention trials in RA will assess AIS scores at baseline and follow‐up visits (171,177–179).…”
Section: Athens Insomnia Scalementioning
confidence: 99%
“…Bunge. is a frequently used traditional Chinese medicine with antiviral and antioxidant activities and a variety of biological functions, 11 and its compound preparations, such as Huangqi Guizhi Wuwutang and Xinfeng capsule granules, are often used for the treatment of RA clinically 12,13 . In addition, with the development of technology and research methods, increasing numbers of traditional Chinese medicine components, including alkaloids, coumarins, flavonoids, saponins and so on, have been identified and purified 14 .…”
Section: Introductionmentioning
confidence: 99%